No adverse safety or virological changes 2 years following vorinostat in HIV-infected individuals on antiretroviral therapy. (15th May 2017) - Mota, Talia M.; Rasmussen, Thomas A.; Rhodes, Ajantha; Tennakoon, Surekha; Dantanarayana, Ashanti; Wightman, Fiona; Hagenauer, Michelle; Roney, Janine; Spelman, Tim; Purcell, Damian F.J.; McMahon, James; Hoy, Jennifer F.; et al.
Abstract : Objective: To determine the long-term effects of vorinostat on safety and virological parameters in HIV-infected individuals on suppressive antiretroviral therapy (ART). Design: Prospective longitudinal observational extended follow-up of 20 HIV-infected individuals on ART previously enrolled in a clinical trial of daily vorinostat 400 mg for 14 days. Extended follow-up included visits at 6, 12, 18 and 24 months postenrolment in the initial clinical trial. Methods: Cell-associated unspliced HIV RNA, total HIV DNA and plasma HIV RNA were quantified by PCR, and CD4 + and CD8 + T cells quantified by flow cytometry. Changes over time in each parameter were assessed using the Wilcoxon matched pair signed-rank test and generalized estimating equations for trend modelling. Results: We recorded a total of 31 adverse events (26 grade 1 and five grade 2) in all study participants ( n = 20). There were no significant changes in the number of CD4 + or CD8 + T cells or plasma HIV RNA over time. In 12 participants for whom baseline samples were available, there were no significant changes in total HIV DNA, cell-associated unspliced HIV RNA, plasma RNA or CD4 + and CD8 + T cells at 6, 12, 18 or 24 months. Conclusion: Extended follow-up for 24 months did not reveal any long-term toxicity or changes in markers of HIV persistence or transcription in participants on ART who had received 14 days of vorinostat. Abstract : Supplemental Digital Content is available in the text